Design of Innovation For Islamic Religious Education Curriculum Based on Antibullying Values - Faishol, Muhammad; Wasino, Wasino; Fakhruddin, Fakhruddin; Asrori, Asrori (Proceedings of International Conference on Science, Education, and Technology, 2024)
Islamic Religious Education curriculum has evolved with innovative elements rooted in Islamic teachings. Indonesia faces significant challenges with bullying, notably highlighted by the Indonesian Child Protection Commission (KPAI), reporting approximately 3,800 cases in 2023, half of which occurred in educational settings, including pesantrens. This literature review explores integrating anti-bullying education into the Islamic Religious Education Curriculum to enhance its role in cultivating values that effectively counteract bullying. By aligning with Islamic principles of compassion and humanity, the study aims to propose practical curriculum development strategies for creating a supportive and inclusive educational environment. The study utilizes a literature review approach, synthesizing data from scholarly sources such as journals, e-books, research reports, and books. This comprehensive review consolidates knowledge on bullying prevention strategies and Islamic educational principles to inform curriculum innovation. Integrating anti-bullying values into the Islamic Religious Education Curriculum is not only feasible but also beneficial. It aligns with Islamic ethical frameworks and addresses pressing societal issues like bullying in educational contexts. By emphasizing empathy, kindness, and conflict resolution rooted in Islamic teachings, the curriculum can mitigate the negative impacts of bullying, fostering healthier social dynamics and improving overall student well-being. This research underscores the pivotal role of curriculum development in promoting a culture of respect and tolerance, fostering a harmonious learning environment conducive to academic success and emotional growth.